In silico and in vitro cytotoxicity profile of hydroalcoholic extract/ fraction(s) of Pachygone ovata - Jeswiny Rodrigues, Kiran Kumar Hullatti, Pukar Khanal (Journal of Applied Pharmaceutical Science, 2020)
Medicinal plants have been used in the past for the treatment of diseases and continue to be an important reservoir for the development of new drugs. With the increasing burden of cancer globally, there is a need to find newer anticancer agents. The process of identification and evaluation of cytotoxic molecules from plants can be achieved conveniently by using simple yet reliable screening models and combining with in silico techniques. Pachygone ovata, least explored plant from Menispermaceae family, is known to be rich in alkaloids. This study aimed to identify the cytotoxic constituents from Pachygone ovata through bioactivity-guided fractionation using Brine shrimp lethality bioassay as a screening model. The active fraction in this assay was evaluated for its in vitro cytotoxic activity on human tumor cell lines. Some reported alkaloids were studied for their binding affinities with topoisomerase II by molecular docking. The study revealed the cytotoxic constituents from P. ovata. The study also revealed alkaloids with higher binding affinity with topoisomerase II, and the scope for further use leads to the development of new drugs.
Keywords: Bisbenzylisoquinoline, brine shrimp, Menispermaceae, MTT, topoisomerase.